2023
DOI: 10.3390/nu15102274
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Kiwifruit Consumption on the Sleep and Recovery of Elite Athletes

Abstract: Background: Poor sleep and resultant under-recovery can negatively impact training adaptations, increase the risk of injury and reduce subsequent performance. Due to the ‘food first’ approach adopted by many athletes, there is scope for investigation of ‘functional food’ based interventions (i.e., kiwifruit contains melatonin which plays a role in circadian rhythm regulation) designed to promote athlete recovery and/or enhance sleep quality and quantity. Methods: Following the baseline assessment (Week 1) all … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 63 publications
(104 reference statements)
0
4
0
Order By: Relevance
“…56 The impact of kiwifruit consumption on the sleep and recovery of elite athletes. 57 Under the supervision of TST (16.9%) and SE (2.4%), it was considerably seen in wrist activation, while recording mental sleep memories revealed a significant decline in WASO and SOL. Kiwi's high folate content may lead to better sleep.…”
Section: The Role Of Nutrition On Sleepmentioning
confidence: 95%
See 2 more Smart Citations
“…56 The impact of kiwifruit consumption on the sleep and recovery of elite athletes. 57 Under the supervision of TST (16.9%) and SE (2.4%), it was considerably seen in wrist activation, while recording mental sleep memories revealed a significant decline in WASO and SOL. Kiwi's high folate content may lead to better sleep.…”
Section: The Role Of Nutrition On Sleepmentioning
confidence: 95%
“…Athletes who fatigue more quickly (in terms of enough sleep and mental issues) have a higher chance of injury and making more mistakes while training and making decisions. 57 This significantly influences our kids since more than 3.5 million young children 12 Science Progress 106(4)…”
Section: Impact Of Sleep and Injury Reducementioning
confidence: 99%
See 1 more Smart Citation
“…As several nutrients interact with neurotransmitters that help regulate the sleep–wake cycle, there is a growing interest in dietary strategies that promote sleep [ 7 ]. For example, recent research has shown that supplementation with phytochemicals such as tart cherries [ 8 ], or kiwi fruit [ 9 ], which are both rich in the sleep promoting hormone melatonin, may enhance sleep quality in humans. In addition, high glycaemic index carbohydrates [ 10 , 11 ] and α-lactalbumin [ 12 , 13 ] before bedtime may reduce sleep onset latency, increase sleep efficiency, and extend total sleep time, via their effects on the amino acid tryptophan.…”
Section: Introductionmentioning
confidence: 99%